2011
DOI: 10.1142/s0219265911003003
|View full text |Cite
|
Sign up to set email alerts
|

Strong Matching Preclusion for the Alternating Group Graphs and Split-Stars

Abstract: The strong matching preclusion number of a graph is the minimum number of vertices and edges whose deletion results in a graph that has neither perfect matchings nor almost-perfect matchings. This is an extension of the matching preclusion problem and has recently been introduced by Park and Ihm.15 In this paper, we examine properties of strong matching preclusion for alternating group graphs, by finding their strong matching preclusion numbers and categorizing all optimal solutions. More importantly, we prove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…In this paper, we study -connectivity of the n-dimensional alternating group graph AG n and the n-dimensional splitstars S 2 n (defined later in Section II), which were introduced by Jwo et al [33] and Cheng et al [16], respectively, for serving as interconnection network topologies of computing systems. The two families of graphs have received much attention because they have many nice properties such as vertex-transitive, strongly hierarchical, maximally connected (i.e., the connectivity is equal to its regularity), and with a small diameter and average distance.…”
Section: B Literature Related To Alternating Group Graph and Split-starsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this paper, we study -connectivity of the n-dimensional alternating group graph AG n and the n-dimensional splitstars S 2 n (defined later in Section II), which were introduced by Jwo et al [33] and Cheng et al [16], respectively, for serving as interconnection network topologies of computing systems. The two families of graphs have received much attention because they have many nice properties such as vertex-transitive, strongly hierarchical, maximally connected (i.e., the connectivity is equal to its regularity), and with a small diameter and average distance.…”
Section: B Literature Related To Alternating Group Graph and Split-starsmentioning
confidence: 99%
“…In particular, Cheng et al [14] showed that alternating group graphs and split-stars are superior to the n-cubes and star graphs under the comparison using an advanced vulnerability measure called toughness, which was defined in [22]. For the two families of graphs, many researchers were attracted to study fault tolerant routing [12], fault tolerant embedding [5], [6], [42], matching preclusion [2], [11], restricted connectivity [15], [25], [35], [36], [48] and diagnosability [10], [25], [30], [34]- [36], [41]. Moreover, alternating group graphs are also edge-transitive and possess stronger and rich properties on Hamiltonicity (e.g., it has been shown to be not only pancyclic and Hamiltonian-connected [33] but also panconnected [6], panpositionable [40] and mutually independent Hamiltonian [39]).…”
Section: B Literature Related To Alternating Group Graph and Split-starsmentioning
confidence: 99%
See 1 more Smart Citation
“…Proposition 2.1. [4] Let G be a r-regular even graph with r ≥ 2. Suppose that smp(G) = r. Then every basic optimal strong matching preclusion set is trivial.…”
Section: Preliminariesmentioning
confidence: 99%
“…Park and Ihm [8] also studied the problem of strong matching preclusion under the condition that no isolated vertex is created as a result of faults, and established the conditional strong matching preclusion number for the class of restricted hypercube-like graphs, which include most non bipartite hypercube-like networks found in the literature. SMP numbers of augmented cubes, arrangement graphs, alternating group graphs and split-star, pancake graphs, 2 -matching composition networks, k -ary n cubes, n-dimensional torus networks, k-composition networks are also investigated; see [1,[9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%